Epidemiological Profile of Vitamin D Deficiency Among Diabetes Mellitus Type-2 Patients - Suman Kotwal; Amarjeet Singh; Anna Javed; Ashima Badyal; Vishal R Tandon; Annil Mahajan (JK Science)
Background: Vitamin D deficiency is a worldwide epidemic health problem. Variable results are available, with few studies favouring and others denying the association of Vitamin D deficiency and Diabetes mellitus Type-2. Material and Methods: An Epidemiological prospective Cross-sectional 3-year observational study was conducted to determine the point prevalence of vitamin D deficiency among Diabetes mellitus Type-2 patients in comparison to age, sex matched healthy controls among the urban and rural population of the Jammu region, and also to evaluate the correlation between vitamin D deficiency and Diabetes mellitus Type-2. Group 1 (n = 1314) patients of Diabetes mellitus Type-2 with any co-morbid profile with or without complications, presenting in a tertiary care medical college. Group 2 (n=1005) age sex matched healthy subjects. Results: The study included 2319 subjects (1314 cases and 1005 controls), Prevalence rates of vitamin D sufficiency (>30 ng/mL), insufficiency (20-30 ng/mL), and the deficiency (<20 ng/mL) were 15.37%, 18.9%, and 65.6% in Diabetes mellitus Type-2, and 19.7%, 19.3%, and 60.9% in non-diabetics, respectively. The Mantel-Haenszel Chi-Square test (MH Chi-Sq. value = 8.105, CI=95%, p=0.016) indicated a significant linear trend between vitamin D levels and Diabetes mellitus Type-2 . Conclusion: The study documented high prevalence of Vitamin D Deficiency both in Diabetes mellitus type-2 patients and healthy control population. This study found a significant association between Vitamin D levels and Diabetes mellitus Type-2.